2018
DOI: 10.1177/0266666918754937
|View full text |Cite
|
Sign up to set email alerts
|

Can community-based organisations deliver adequate agricultural information to farmers? Evidence from rural resources centres in Cameroon

Abstract: Rural Resources Centres (RRCs) managed by community-based organisations, where farmers come together for training and demonstration, have been an innovative extension approach in Cameroon since 2006. This paper describes information flow in RRCs and farmers’ assessment of RRCs as information sources. All the RRCs in Cameroon were studied and 29 group interviews, involving 118 producers and 7 individual interviews with RRC managers, were performed. RRCs share information with several stakeholders including farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…There are obvious changes in employment, income and social relations [17]. The resource endowment of farmers is diversified, including economic, land, information and social aspects [18]. Therefore, in the design of the resource endowment index system, it should be widely and comprehensively considered.…”
Section: Building the Measurement Model Of Rural Resources Endowmentmentioning
confidence: 99%
“…There are obvious changes in employment, income and social relations [17]. The resource endowment of farmers is diversified, including economic, land, information and social aspects [18]. Therefore, in the design of the resource endowment index system, it should be widely and comprehensively considered.…”
Section: Building the Measurement Model Of Rural Resources Endowmentmentioning
confidence: 99%
“…In Cameroon, the information flow in Rural Resources Centres (RRCs) and the rating of such information sources by Cameroonian farmers were explored, and it was found that farmers rate their fellow farmers as the primary agricultural information source while RRCs come second [64]. In Ghana, the determining variables of mobile-phone utilization by smallholder poultry farmers were assessed.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Inclusive entrepreneurial opportunities are different from entrepreneurial opportunities in general sense. Opportunities appear in specific areas and are strongly influenced by background factors, such as regional cluster environment and government [ 10 ]. Oladele et al think that natural conditions, history, accidental factors, economies of scale and externalities, enterprise organizational structure, competition, and innovation are the key factors for the formation of industrial clusters [ 11 ].…”
Section: Related Workmentioning
confidence: 99%